MILIK PEMERINTAH ACEH SEBAGAI BADAN LAYANAN UMUM DAERAH . - Suhaimi, Husni A. Jalil, Eddy Purnama. (Jurnal Ilmu Hukum, 2015)
Abstract: The implementation of the Appointment of the Children and Mother Hospital Belonging to Aceh Government, the Aceh Governor has established Reviewer Team to asses the Hospital to be increased its fund management becomes to Regional Public Service. After being verified towards technical requirements and administrative as ruled by the Government Regulation Number 23, 2005 regarding the Management of Fund at the Public Service institution and the Home Minister Affair Regulation Number 61, 2007 regarding the Guidance of Fund Management at Regional Public Service Institution, the hospital has been determined as Regional Public Service and has been determined as Regional Public Service, in its implementation of the review on documents submitted by the Management of the Hospital to Aceh Governor is actually not accordance with existing mechanism as there are technical requirement relating financial report and final report audit as administrative requirement is not provided during the assessment, nevertheless, the team persist to submit it to the Governor to determine the Hospital and the financial management is not suitable to the standard of the management of regional public service. Keywords : Regional Public Service, Financial Management Method, and Hospital. Abstrak: Pelaksanaan Penetapan Status Rumah Sakit Ibu dan Anak Milik Pemerintah Aceh, Gubernur Aceh membentuk tim penilai kelayakan Rumah Sakit Ibu dan Anak untuk ditingkatkan pengelolaannya menjadi Badan Layanan Umum Daerah. Setelah dilakukan verifikasi terhadap dokumen persyaratan teknis dan administrasi sebagaimana ditentukan di dalam Peraturan Pemerintah Nomor 23 Tahun 2005 tentang Pengelolaan Keuangan Badan Layanan Umum dan Peraturan Menteri Dalam Negeri Nomor 61 Tahun 2007 tentang Pedoman Teknis Pengelolaan Keuangan Badan Layanan Umum Daerah, Rumah Sakit Ibu dan Anak telah ditetapkan sebagai Badan Layanan Umum Daerah, dalam pelaksanaan penilaian dan pengkajian dokumen-dokumen yang diusulkan oleh Manajemen Rumah Sakit Ibu dan Anak kepada Gubernur Aceh sebenarnya belum sesuai dengan mekanisme yang berlaku karena ada persyaratan teknis menyangkut dengan laporan kinerja keuangan dan laporan audit terakhir yang merupakan persyaratan administratif tidak dilengkapi pada saat dilakukan penilaian, namun Tim Penilai tetap merekomendasikan kepada Gubernur Aceh untuk menetapkan Rumah Sakit Ibu dan Anak sebagai Badan Layanan Umum Daerah dan dalam tata kelola keuanganpun belum memenuhi standar pola pengelolaan keuangan badan layanan umum daerah. Kata kunci : Badan Layanan Umum Daerah, Pola Pengelolaan Keuangan, Rumah Sakit.